A comparative study of natural variation in hemolymph glucose levels under different dietary sugar conditions in Drosophila melanogaster and D. simulans. - Inomata, N.; Miyazaki, M.; Noguchi, M.; Itoh, M. (Genes & Genetic Systems, 2023)
Physiological responses to environmental changes play important roles in adaptive evolution. In particular, homeostatic regulatory systems that maintain constant circulating glucose levels are crucial in animals. However, variation in circulating glucose levels and the genetic effects on phenotypic variation in natural populations remain to be clarified. Here, we investigated the hemolymph glucose levels in natural populations of Drosophila melanogaster and its sibling species, D. simulans, in Japan. We quantified hemolymph glucose concentrations in third instar larvae of 27 lines for each species, which were reared on either glucose-free or glucose-rich food. In both species, genetic variation was not a major component of phenotypic variation on either glucose-free or glucose-rich food. The hemolymph glucose concentrations were much higher in D. simulans than in D. melanogaster. Genetic variance was larger in D. simulans than in D. melanogaster. The observed differences between the two species may be associated with the much more recent colonization history of D. simulans populations in Japan and/or the tolerance to environmental stresses. Our findings suggest that natural selection acting on hemolymph glucose levels in D. melanogaster is different from that in D. simulans.